Solução analítica do potencial de Morse em mecânica clássica - Barboza, F.L. Moraes [UNESP] (2007)
Usually the Morse potential is studied in the quantum mechanics context. On the other hand, there are relatively few applications for classical problems. In this work, a complete solution for the classical equation of motion is found for a particle subject to this potential. Numerical examples are presented for a fixed set of parameters. Copyright by the Sociedade Brasileira de Física.